Mata pelajaran produktif, prakerin dan motivasi belajar : kesiapan kerja siswa - Naim Naim (Jurnal Riset Pendidikan Ekonomi, 2022)
The purpose of this study was to determine the effect between the independent variable and the dependent variable either partially or simultaneously. The population according to Arikonto (2010:173) is the entire research subject. Population research is done if the researcher wants to see all the elements in the population. The population in this study were all students of class XI SMK Islam Donomulyo Malang Regency in the 2021/2022 academic year which consisted of 2 classes totaling 65 students. Data was collected by using questionnaires and documentation methods. Validity test with Product moment technique and Alpha Crombach reliability test, test data analysis requirements using classical assumption test and multiple linear regression analysis. Hypothesis testing using t test and F test. The results of this study show that there is a significant effect of the variable mastery of productive subjects, industrial work practices (prakerin) and learning motivation on the work readiness of class XI students at SMK Islam Donomulyo Malang Regency in the 2021/2022 academic year. of 49.905%. There is a significant influence on the mastery of productive subjects on the work readiness of class XI students at the Donomulyo Islamic Vocational School, Malang Regency, for the 2021/2022 academic year by 51.31%. There is an influence of prakerin on the work readiness of class XI students at Islamic Vocational School Donomulyo, Malang Regency in the academic year 2021/2022 by 31.84%, There is a significant influence of learning motivation on the work readiness of class XI students at SMK Islam Donomulyo, Malang Regency in the Academic Year 2021/2022 by 33.05%.